2014
DOI: 10.1073/pnas.1406234111
|View full text |Cite
|
Sign up to set email alerts
|

Strand-specific (asymmetric) contribution of phosphodiester linkages on RNA polymerase II transcriptional efficiency and fidelity

Abstract: Nonenzymatic RNA polymerization in early life is likely to introduce backbone heterogeneity with a mixture of 2′-5′ and 3′-5′ linkages. On the other hand, modern nucleic acids are dominantly composed of 3′-5′ linkages. RNA polymerase II (pol II) is a key modern enzyme responsible for synthesizing 3′-5′-linked RNA with high fidelity. It is not clear how modern enzymes, such as pol II, selectively recognize 3′-5′ linkages over 2′-5′ linkages of nucleic acids. In this work, we systematically investigated how phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…We observed three strong pol II pausing sites near the 2′-5′ dT site (pausing at 10–12 nt positions). However, pol II can eventually bypass the 2′-5′ dT linkage site to generate longer transcripts upon extended incubation as previously observed ( 30 ). Taken together, we revealed that pol II tolerates 3′-5′ rU substitution (sugar backbone heterogeneity), whereas a single substitution with 2′-5′ rU causes strong block for pol II elongation.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…We observed three strong pol II pausing sites near the 2′-5′ dT site (pausing at 10–12 nt positions). However, pol II can eventually bypass the 2′-5′ dT linkage site to generate longer transcripts upon extended incubation as previously observed ( 30 ). Taken together, we revealed that pol II tolerates 3′-5′ rU substitution (sugar backbone heterogeneity), whereas a single substitution with 2′-5′ rU causes strong block for pol II elongation.…”
Section: Resultssupporting
confidence: 66%
“…Previous studies have revealed the molecular basis of how RNA pol II recognizes functional groups and structural features of nucleic acids during transcription ( 25 29 ). Particularly, our very recent work used a synthetic 2′-5′ DNA template as a model to dissect the phosphodiester linkage impact on pol II transcription ( 30 ). However, it is unclear how pol II processes the template DNA containing ‘natural’ backbone heterogeneity (3′-5′DNA, 3′-5′ RNA and 2′-5′ RNA), which could exist during evolution and whether pol II recognizes these three types of backbone differently.…”
Section: Introductionmentioning
confidence: 99%
“…Our qPCR data showed that a single 2 ′ ,5 ′ -linked ribonucleotide in a DNA template decreases DNA synthesis by a factor of 5. Consistent with the findings of Xu et al (2014Xu et al ( , 2015, these data indicate that 2 ′ ,5 ′ -linked ribonucleotides in genomic DNA templates would slow down DNA replication and transcription in prokaryotic and eukaryotic cells. Moreover, because RNA 2 ′ ,5 ′ linkages are not a substrate for RNase H (Kandimalla et al 1997), it is likely that such rNMPs would not be removed by the cellular type 2 RNase H-initiated repair mechanism (Williams and Kunkel 2014;Williams et al 2016) and would persist in DNA.…”
Section: Nucleic Acid-specific Coding Potential Of the Branchpointsupporting
confidence: 82%
“…A backbone heterogeneity with 2 ′ ,5 ′ -linked RNA is thought to exist in DNA during molecular evolution (Xu et al 2015). Whether contemporary template-dependent nucleic acid polymerases still tolerate 2 ′ ,5 ′ -linked rNMPs in DNA (Xu et al 2014(Xu et al , 2015 has become of interest. Our qPCR data showed that a single 2 ′ ,5 ′ -linked ribonucleotide in a DNA template decreases DNA synthesis by a factor of 5.…”
Section: Nucleic Acid-specific Coding Potential Of the Branchpointmentioning
confidence: 99%
“…These nucleic acid analogs enabled us to investigate the individual contributions of the nucleobase and sugar moieties to pol II transcription. These studies have advanced our understanding of how the intrinsic structural features of nucleic acid moieties are recognized and how specific interactions are involved in substrate selection and incorporation during pol II transcription ( 21 24 ). However, the interactions involved at the triphosphate moiety of NTPs during nucleotide selection and incorporation have not yet been extensively explored.…”
Section: Introductionmentioning
confidence: 99%